The effectiveness of unmanned aerial vehicle (UAV) for digital slope mapping - Mohd Fakhrurrazi, Ishak; M. F., Zolkepli; Nurmunira, Muhammad (Penerbit Universiti Malaysia Pahang, 2020)
This paper discusses the applications of unmanned aerial vehicle (UAV) for slope mapping and its important parameters including perimeter, area and volume of certain selected areas. Modern UAV able to take high quality image which essential for the effectiveness and nature of normal mapping output such as Digital Surface Model (DSM) and Digital Orthophoto. This photo captured by UAV will later transfer to commercial software to generate full map of study area. Three locations in Kuantan Pahang are chosen (Sungai Lembing, Politeknik Sultan Ahmad Shah ‘POLISAS’ and Pahang Matriculation College) for slope mapping. With the help of established software, the measurement (perimeter, area and volume) of selected study areas can be determined easily and considered as the main interest in this study. In addition, another outcome of this study is, this modern method of mapping will be compare to traditional method of mapping which proven to be more effective in term of low costing, low time consuming, can gather huge amount of data within short period of time, low man power needed and almost no potential risk of hazardous effect to man. In conclusion, modern technology of UAV proves to be very effective for mapping in geotechnical engineering. Slope mapping help researchers and engineers to obtain slope measurement within short period of time compare to previous traditional method.